MANAJEMEN INFORMASI KEUANGAN PENDIDIKAN ISLAM: PERAN SISTEM INFORMASI UNTUK DANA BOS, ZAKAT, DAN WAKAF PENDIDIKAN - Mesyitahsyare; Rafika Amelia Fitri; Dina Hermina (Jurnal Riset Multidisiplin Edukasi, 2026)
Transparent, accountable, and integrated financial management is a critical prerequisite for ensuring the sustainability and quality improvement of Islamic education. Islamic educational institutions manage diverse sources of funding, including government-provided School Operational Assistance (BOS) as well as socio-religious funds such as zakat and educational waqf, each of which has distinct characteristics and management mechanisms. This article aims to analyze the role of information systems in Islamic education financial information management and to examine their contribution to enhancing efficiency, transparency, and accountability in the management of BOS, zakat, and waqf funds. This study employs a literature review method by examining relevant scholarly publications, regulations, and previous research findings. The results indicate that the implementation of technology-based financial information systems enables the integration of financial planning, budgeting, implementation, monitoring, and reporting processes in a more systematic and real-time manner, thereby supporting more accurate and data-driven decision-making. Nevertheless, the implementation of such systems still faces several challenges, including limited human resource capacity, inadequate technological infrastructure, and the lack of integrated and standardized cross-system data management. Therefore, strengthening human resource competencies, investing in information technology, and developing interoperable and standardized systems are essential to achieving professional, sustainable, and Sharia-compliant financial governance in Islamic education institutions.